Use of Biofeedback Combined With Diet for Treatment of Obstructed Defecation Associated With Paradoxical Puborectalis Contraction (Anismus): Predictive Factors and Short-term Outcome. Issue 2 (February 2016) - Murad-Regadas, Sthela M.; Regadas, Francisco S. Pinheiro; Bezerra, Carla C. Rocha; de Oliveira, Maura T. Coutinho Cajazeiras; Regadas Filho, Francisco S. Pinheiro; Rodrigues, Lusmar Veras; Almeida, Saulo Santiago; da Silva Fernandes, Graziela O.
Abstract : BACKGROUND: Numerous studies have described the use of biofeedback therapy for the treatment of anismus. Success rates vary widely, but few data are available regarding factors predictive of success. OBJECTIVE: Our aim was to evaluate short-term results of biofeedback associated with diet in patients with obstructed defecation because of anismus and to investigate factors that may affect the results. DESIGN: Patients were identified from a single-institution prospectively maintained database. SETTINGS: This study was conducted in a tertiary hospital. PATIENTS: Consecutive patients who had obstructed defecation associated with anismus and were treated with biofeedback associated with diet were eligible. INTERVENTIONS: Each patient underwent anal manometry and/or dynamic anal ultrasound. Patients with anismus and were treated with biofeedback associated with diet. MAIN OUTCOME MEASURES: Patients classed as having a satisfactory response to therapy and those classed as having an unsatisfactory response were compared with regard to sex, age, Cleveland Clinic Florida constipation score, functional factors (anal resting and squeeze pressures and reversal of paradoxical puborectalis contraction on manometry), and anatomic factors in women (history of vaginal delivery, number of vaginal deliveries, menopause, hysterectomy, and previous anorectal surgery). RESULTS: A total of 116 patients were included (75 women and 41 men). Overall, 59% were classed as having a satisfactory response (decrease in constipation score, >50%). Patients with satisfactory responses to biofeedback plus diet did not differ from those with unsatisfactory responses with regard to clinical, anatomic, and physiological factors. LIMITATIONS: This was not a randomized controlled trial. CONCLUSIONS: Biofeedback combined with diet is a valuable treatment option for patients with obstructed defecation syndrome associated with anismus, and more than half of our patients of both sexes achieved a satisfactory response. Improvement was not related to reversal of paradoxical contraction of puborectalis muscles at manometry. Patient sex, age, previous anorectal surgery, anorectal manometry pressures, and vaginal delivery, menopause, and hysterectomy in women did not significantly affect outcome.